2015
DOI: 10.1111/joor.12322
|View full text |Cite
|
Sign up to set email alerts
|

Management of sleep bruxism in adults: a qualitative systematic literature review

Abstract: This paper updates the bruxism management review published by Lobbezoo et al. in 2008 (J Oral Rehabil 2008; 35: 509-23). The review focuses on the most recent literature on management of sleep bruxism (SB) in adults, as diagnosed with polysomnography (PSG) with audio-video (AV) recordings, or with any other approach measuring the sleep-time masticatory muscles' activity, viz., PSG without AV recordings or electromyography (EMG) recorded with portable devices. Fourteen (N = 14) papers were included in the revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 41 publications
1
131
1
15
Order By: Relevance
“…And finally, as soon as the specific indications for treatment are defined, the potential for the use of smartphone‐EMA approaches as a strategy to implement cognitive‐behavioural management of AB could be assessed. Indeed, it could be possible that someone who notices to be an AB bruxer could actually try to stop his/her own oral behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…And finally, as soon as the specific indications for treatment are defined, the potential for the use of smartphone‐EMA approaches as a strategy to implement cognitive‐behavioural management of AB could be assessed. Indeed, it could be possible that someone who notices to be an AB bruxer could actually try to stop his/her own oral behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal bruxism (NB) is defined as abnormal maxillomandibular activity during sleep, characterized by grinding and clenching of the teeth [1, 2]. NB can lead to wear on the teeth, dental prostheses/implant failure, tooth sensitivity, pain in the teeth, jaw, masticatory muscle, and temporomandibular joint (TMJ), neck pains and headache, periodontal disease, oral or facial pain, and potentially tooth loss [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…In two comprehensive review studies, Tinastepe et al [1] and Manfredini et al [2] suggested that there is not enough evidence to use botulinum injection in the treatment of bruxism. The purpose of the present study was to investigate the potential performance of BTXA on nocturnal bruxism and to share this clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Within these premises, SB may have clinical consequences for the stomatognathic system (eg, tooth wear, temporomandibular joint (TMJ) and/or masticatory muscle pain, headaches, complications in prosthodontic rehabilitation) that have been systematically reviewed over the past several years . From a clinician's approach, SB should be viewed as a condition that requires management only when it has consequences, as a danger of overtreatment exists . General treatment approaches include behavioural strategies, pharmacotherapy and intra‐oral devices; however, the control of SB itself is exceedingly difficult and, unfortunately, none of the techniques can permanently “cure” or “stop” it …”
Section: Introductionmentioning
confidence: 99%